Cutaneous Plasmacytosis: A Clinicopathologic Study of a Series of Cases and Their Treatment Outcomes. (January 2018) - Han, Xiuhui Debra; Lee, Siong See Joyce; Tan, Suat Hoon; Chong, Wei-Sheng; Ng, See Ket; Ooi, Melissa Gaik Ming; Goh, Chee Leok
Abstract : Introduction: Cutaneous plasmacytosis (CP) is a rare skin disorder characterized by multiple reddish brown nodules with polyclonal plasma cell proliferation. It has most often been reported to affect the trunk but is also known to affect the face and extremities in adults and is predominantly seen in Asians. The etiology is poorly understood, and there is no consensus on treatment methods. Methods: Five cases diagnosed to have CP were collated from our institution. Their clinicopathologic features and treatment outcomes were reviewed. Results: Four of the 5 patients presented with lesions that affected multiple sites of the body including the trunk, axillae, face, and limbs. The remaining patient had lesions localized to his axillae. The lesions were generally asymptomatic. All patients had hypergammaglobulinaemia but only one had a faint monoclonal band detected on immunofixation. Common findings in the biopsy results for all patients were perivascular plasma cell infiltrates without light chain restriction on kappa/lambda staining, as well as mast cell infiltrates. Partial remission of cutaneous lesions was observed in 3 of the patients, with 2 of them responding well to psoralen and ultraviolet A radiation therapy. Conclusion: CP presents with distinctive clinical features and characteristic histological features including polyclonal perivascular plasma cell infiltrates. The axilla seems to be a frequent and characteristic site of involvement and may be a useful clinical clue to the condition. In the management of patients with CP, it is important to exclude secondary causes of plasmacytic infiltrates. While there are no clearly established treatment modalities for CP, psoralen and ultraviolet A radiation therapy may be a viable option in view of the clinical improvement observed in our patients who received it.